Showcasing a Smart Water Network Based on an Experimental Water Distribution System. (2015) - Günther, M.; Camhy, D.; Steffelbauer, D.; Neumayer, M.; Fuchs-Hanusch, D.
Abstract: Nowadays, modern utilities have installed a variety of measurement devices like pressure sensors, flow meters, noise loggers, water quality sensors for different intentions. In this paper we introduce an experimental water distribution system (EWDS-TUG) that serves as an example of implementing a smart water network solution. The used EWDS-TUG states a highly determined water supply system. Artificial customers are installed and can be controlled automatically by magnetic valves. We present how we collect sensor data and control magnetic valves installed, remotely via a web based control and communication solution, which is deeply integrated in the measurement workflow.